Arte computacional: preservação e arquivamento na contemporaneidade - Dalla Costa, Cristina Landerdahl (2019)
This dissertation is about a computational art preservation study in the contemporary context and some procedures used to maintain the artistic and cultural memory. Five museum-like institutions were chosen for the research, with an example of preserved art work, like: Itaú Cultural, from São Paulo (Brazil), with the artwork Desertesejo (2000) by Gilbertto Prado; MoMA, from New York (USA), with the artwork Pac Man (1980) by Toru Iwatani; ZKM, from Karlsruhe (Germany), with the artwork The Legible City (1989-1991) by Jeffrey Shaw; Solomon R. Guggenheim Foundation, from New York (USA), with the artwork TV Garden (1974/2000) by Nam June Park; and Reina Sofía, from Madrid (Spain), with the artwork 6 TV Dé-Coll/age (1963) by Wolf Vostell. The case study of the webart/installation Desertesejo (2000) is presented, which was developed in the New Rumos New Media Program of Itaú Cultural, in São Paulo. Aspects that make difficult the creation of parameters for the preservation and the archiving of art works are analyzed, for instance, the variety of artistic languages, devices, equipment, materials, and analogical or digital procedures, different technological apparatuses that are used, besides the specific terminology to classify these projects. This dissertation contributes to the discussion of the preservation of contemporary works that use computational languages in its establishment, emphasizing the various agents' participation involved in this project, trying to maintain the artistic memory of contemporary society.